Examining the Impact of ESG Dimensions on Corporate Financial Performance: Evidence from the Sustainable and Responsible Investment (SRI) Kehati Index - Dinda Amelya; Siti Ridloah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyse the influence of the Environmental, Social, and Governance (ESG) dimension on financial performance for companies listed in the Sustainable and Responsible Investment (SRI) KEHATI Index on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. This research provides an empirical contribution by examining differences in the influence of ESG aggregates and dimensions on the financial performance of sustainability-oriented companies in Indonesia. The research used a quantitative approach based on secondary data from Refinitiv and the financial statements of 22 companies selected through purposive sampling over five years of observation. The data was analysed using panel data regression. Financial performance is measured using indicators of firm value (Tobin’s Q) and profitability (Return on Assets). The study’s results indicate that the ESG aggregate has a positive and significant effect on firm value as measured by Tobin’s Q, and on profitability as measured by ROA. At the dimension level, both the environmental and social dimensions show a negative and significant effect on Tobin’s Q and ROA. This result suggests that increased focus on environmental and social factors may introduce operational challenges and additional costs, thereby adversely affecting financial performance. In contrast, the governance dimension does not exhibit a significant effect on either financial performance indicator. These findings provide implications for investors and management in formulating effective ESG strategies to improve company value and long-term financial performance.